2002
DOI: 10.1002/cne.10302
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of neuronal calcium sensor‐1 in the developing chick retina

Abstract: Neuronal calcium sensor-1 (NCS-1) is a Ca(2+) binding protein that has been implicated in the regulation of neurotransmission and synaptogenesis. In this study we investigated the developmental expression and localization of NCS-1 in the chick retina. Single- and double-labeling experiments with three-dimensional reconstruction as well as ultrastructural data of the distribution of NCS-1 suggest that this protein is also involved in axonal process outgrowth. We found an early expression of NCS-1 in ganglion ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Therefore, the subcellular localization of NCS-1 revealed by the present study suggests that NCS-1 participates in many aspects of neuronal activity, including neurotransmission and synaptogenesis, in the developing rat spinal cord, as it appeared in neuronal cell bodies, dendrites, axons, and presynaptic terminals. This finding is in agreement with the previous studies showing the localization of NCS-1 in both the pre-and postsynaptic sites (Olafsson et al, 1997;Martone et al, 1999;Bergmann et al, 2002;Jinno et al, 2002).…”
Section: Discussionsupporting
confidence: 95%
“…Therefore, the subcellular localization of NCS-1 revealed by the present study suggests that NCS-1 participates in many aspects of neuronal activity, including neurotransmission and synaptogenesis, in the developing rat spinal cord, as it appeared in neuronal cell bodies, dendrites, axons, and presynaptic terminals. This finding is in agreement with the previous studies showing the localization of NCS-1 in both the pre-and postsynaptic sites (Olafsson et al, 1997;Martone et al, 1999;Bergmann et al, 2002;Jinno et al, 2002).…”
Section: Discussionsupporting
confidence: 95%
“…Recent studies have shown that NCS-1 is expressed within neurons of the developing and adult mouse inner ear (Sage et al, 2000), and that NCS-1 mediates survival of neurons within the avian cochlear nucleus (Wilkinson et al, 2003). Based on the pattern of NCS-1 expression, it has been suggested that NCS-1 may be involved in axogenesis and synaptogenesis (Reynolds et al, 2001;Bergmann et al, 2002;Kawaski et al, 2003). We examined apoptosis-mediated cell death in the developing otocysts of ncs-1a morphant embryos using a whole-mount TUNEL assay and found very little cell death in the ncs-1a morphant embryos and their wild-type clutch-mates (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…layer at E5, before ganglion cell synapses in either the retina or tectum (Bergmann et al, 2002). Similarly, in the developing mouse inner ear, NCS-1 is in the vestibular and cochlear afferents before synapse formation (Sage et al, 2000).…”
Section: Ncs-1 and Axon Outgrowthmentioning
confidence: 98%